Comparing health inequalities among men aged 18-65 years in Australia and England using the SF-36. - Clarke, P; Smith, L; Jenkinson, C (2002)
OBJECTIVE: To compare the distribution of the domains and summary scores of the SF-36 health survey by occupation-related social classes in England and Australia for employed males age 18-65 years. METHOD: Relative and absolute measures of inequality based on the concentration index were used to examine the distribution of indicators of reported health based on domains and summary scores of the SF-36 across occupation-related social classes in both countries. RESULTS: The degree of inequality is most pronounced in the domains and summary scores of the SF-36 representing aspects of physical health. In regard to comparisons between these countries, there is no significant difference in the distribution of summary scores for physical health. Although there are differences in the summary scores for mental health, there is no evidence of significant inequality in Australia in this aspect of health. CONCLUSIONS: There is a similar pattern of occupation-related health inequality in the physical health dimensions of the SF-36 health survey for employed males age 18-65 years. IMPLICATIONS: Given the similarities in the distribution of measures of physical health in the two countries, it would be useful to assess recent English policy initiatives aimed at reducing health inequalities when developing interventions to tackle inequalities in Australia.